Clinical significance of altered collagen-receptor functioning in platelets with emphasis on glycoprotein VI. (November 2019) - Nurden, Alan T.
Abstract: Much interest surrounds the receptors α2β1 and glycoprotein VI (GPVI) whose synchronized action mediates the attachment and activation of platelets on collagen, essential for preventing blood loss but also the most thrombogenic component of the vessel wall. Subject to density variations on platelets through natural polymorphisms, the absence of α2β1 or GPVI uniquely leads to a substantial block of hemostasis without causing major bleeding. Specific to the megakaryocyte lineage, GPVI and its signaling pathways are most promising targets for anti-thrombotic therapy. This review looks at the clinical consequences of the loss of collagen receptor function with emphasis on both the inherited and acquired loss of GPVI with brief mention of mouse models when necessary. A detailed survey of rare case reports of patients with inherited disease-causing variants of the GP6 gene is followed by an assessment of the causes and clinical consequences of acquired GPVI deficiency, a more frequent finding most often due to antibody-induced platelet GPVI shedding. Release of soluble GPVI is brought about by platelet metalloproteinases; a process induced by ligand or antibody binding to GPVI or even high shear forces. Also included is an assessment of the clinical importance of GPVI-mediated platelet interactions with fibrin and of the promise shown by the pharmacological inhibition of GPVI in a cardiovascular context. The role for GPVI in platelet function in inflammation and in the evolution and treatment of major illnesses such as rheumatoid arthritis, cancer and sepsis is also discussed.